Anti-Money Laundering and Counter-Terrorism Financing Amendment Bill 2017 [Provisions] - Australia. Parliament. Senate. Legal and Constitutional Legislation Committee; Macdonald, Ian, 1945- ([Canberra] : Senate Legal and Constitutional Legislation Committee, 2017)
"Amends the: Anti-Money Laundering and Counter-Terrorism Financing Act 2006 to: expand the objects of the Act to reflect the domestic objectives of anti-money laundering and counter-terrorism financing regulation; expand the scope of the Act to include regulation of digital currency exchange providers; clarify due diligence obligations relating to correspondent banking relationships and broadening the scope of these relationships; qualify the term 'in the course of carrying on a business'; allow related bodies corporate to share information; expand the range of regulatory offences for which the AUSTRAC Chief Executive Officer (CEO) is able to issue infringement notices; allow the CEO to issue a remedial direction to a reporting entity to retrospectively comply with an obligation that has been breached; give police and customs officers broader powers to search and seize physical currency and bearer negotiable instruments and establish civil penalties for failing to comply with questioning and search powers; revise certain definitions; and clarify certain powers and obligations of the CEO; and Anti-Money Laundering and Counter-Terrorism Financing Act 2006 and Financial Transaction Reports Act 1988 to de-regulate the cash-in-transit sector, insurance intermediaries and general insurance providers." -- publisher's website.
"October 2017"
Chair: Ian Macdonald.
Includes bibliographical references.
Also available online. Address as at 15/1/18
Keywords: Money laundering -- Australia -- Prevention; Terrorism -- Australia -- Prevention; Terrorism -- Finance -- Law and legislation -- Australia; Australian